Parasitic wasps related to Prays oleae (Bernard, 1788) (Lepidoptera, Praydidae) in olive orchards in Greece - Eleftherios Alissandrakis; Panagiota Psirofonia; Nickolas G. Kavallieratos; Saša S. Stanković; Vladimir Žikić (ZooKeys, 2018)
The olive moth, Prays oleae (Bernard, 1788) (Lepidoptera: Praydidae) is categorised among the most devastating insect pests of olives, whose anthophagous and carpophagous generations can cause yield loss up to 581 and 846 kg of fruit per ha, respectively. In this study, results of the captured parasitoids in olive tree (Olea europaea Linnaeus, 1753) orchards, or infested olive plant material in Crete, Greece, is presented. Five of the six identified species captured in trap devices are related to P. oleae, i.e., Chelonus elaeaphilus Silvestri, 1908, Chelonus pellucens (Nees, 1816), Apanteles xanthostigma (Haliday, 1834), Diadegma armillatum (Gravenhorst, 1829), and Exochus lentipes Gravenhorst, 1829. The species Eupelmus urozonus Dalman, 1820 and Pnigalio mediterraneus Ferrière & Delucchi, 1957 were reared from infested P. oleae leaves. Chelonus pellucens is reported for the first time from Greece. According to the international literature, 59 hymenopterous and dipterous parasitoid species are associated with P. oleae in Europe.